2008
DOI: 10.1002/pssc.200778527
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium‐based Schottky contacts on n‐doped gallium nitride

Abstract: Electrical characteristics and thermal stability of Rhodium (Rh)‐based Schottky contacts on n‐GaN, including Rh/Au and Ni/Rh/Au, have been investigated and compared with those of the Ni/Au contact. Although the maximum Schottky barrier height (SBH) of the Rh/Au contact is slightly lower than that of Ni/Au, the inclusion of a thin Ni layer to yield the Ni/Rh/Au contact has led to a maximum SBH of 0.80 eV, surpassing that of Ni/Au by 0.07 eV and leading to a reduced reverse leakage current at ‐1 V by 1 order of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 7 publications
0
20
0
Order By: Relevance
“…We have recently reported RuP amorphous alloys grown utilizing the ruthenium trimethylphosphine complex, cisRuH 2 (PMe 3 ) 4 . 34 The incorporation of phosphorous appears to hinder the formation of crystalline Ru and similar effect is postulated to be taking place here.…”
Section: Bond Lengthsmentioning
confidence: 99%
See 4 more Smart Citations
“…We have recently reported RuP amorphous alloys grown utilizing the ruthenium trimethylphosphine complex, cisRuH 2 (PMe 3 ) 4 . 34 The incorporation of phosphorous appears to hinder the formation of crystalline Ru and similar effect is postulated to be taking place here.…”
Section: Bond Lengthsmentioning
confidence: 99%
“…CVD processes can also allow for the selective growth of films that have good step coverage compared with traditional techniques such as PVD. [1][2][3] Thin films of rhodium are used as electrical contacts, 4,5 reflective coatings, 6,7 catalysis, 8,9 and wearresistant coatings for extreme conditions. 2,10 Previous studies have focused on volatile compounds which feature traditional organometallic ligands such as CO, C 2 H 4 , C 5 H 5 , and fluorinated hydrocarbons such as trifluoroacetylacetonate and it has been shown that film quality is dependent on the precursor used.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations